2015
DOI: 10.58221/mosp.v109i2.7930
|View full text |Cite
|
Sign up to set email alerts
|

Language Didactics Dissertations in Sweden 2000 – 2009: A Research Survey

Abstract: This article surveys doctoral dissertations in language education written in Sweden over the ten years from 2000 to 2009. The survey concentrates on foreign languages. 23 dissertations are studied, 12 dealing with English, five with French, two with German, one with Spanish, one with Italian, and two with no specific language. Eighteen of the dissertations principally deal with years seven to nine of primary/lower-secondary school and with upper-secondary school, two deal with language studies at university le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, the number of Ph.D. theses is high compared with the previous period. Tholin (2015) reviewed the Ph.D. theses from the field issued during the period 2000-2009 and found that 23 had been published. In this review, 31 Ph.D. theses and nine Licentiate theses on English or other foreign languages were covered.…”
Section: Desirable Topics For Future Researchmentioning
confidence: 99%
“…For example, the number of Ph.D. theses is high compared with the previous period. Tholin (2015) reviewed the Ph.D. theses from the field issued during the period 2000-2009 and found that 23 had been published. In this review, 31 Ph.D. theses and nine Licentiate theses on English or other foreign languages were covered.…”
Section: Desirable Topics For Future Researchmentioning
confidence: 99%
“…However, it is important to note that the courses within the Swedish system do not equal the levels of CEFR. Rather, the CEFR levels overlap across the courses as seen in Table 2 Themes that can be tied to the idea of focus-on-form assessment in the Swedish EAL context were identified by Tholin (2015), who summarized the Swedish dissertations published on the topic of foreign language education in Sweden between the years 2000 and 2009. Amongst the six themes identified by Tholin, "Assessment of students' oral and written proficiencies" and "Error analysis and transfer" stand out as interesting for the topic of the current dissertation.…”
Section: The English Language Subject In the Swedish Contextmentioning
confidence: 99%